Pemanfaatan Virgin Coconut Oil (VCO) dalam Kehidupan Sehari-Hari di Desa Cemagi Badung Bali - Dewa Ayu Ika Pramitha; Agung Ari Chandra Wibawa (Jurnal Pengabdian UNDIKMA, 2021)
This aims of activity to provide education to the public regarding the use and manufacture of Virgin Coconut Oil (VCO) in daily life on a household scale. These activity is in partnership with Cemagi Village, whose daily life usually makes coconut oil from copra (salted oil). The method used in this service is to provide solutions and knowledge, especially in the health sector, regarding the benefits of VCO in everyday life. Participants in this service program are very enthusiastic to accept and carry out every stage of the proposed program. The stages that have been carried out in this service program have helped to increase the knowledge of the Banjar Sangiangan community of Cemagi Village about the process of making VCO and to know the health benefits generated by consuming VCO.